A Re-examination of the Interpretation of Cypriote Material Culture in the MC III - LC I Period in the Light of Textual Data - Knapp, Arthur Bernard (1979)
PhD diss.; references in Amarna letters and other texts; Order No. 80-00, 403. Cf. DissAbstr 40 (1980) 4169-A.